PENINGKATAN KEMAMPUAN MEMAHAMI CERITA DONGENG MELALUI METODE DISKUSI PADA SISWA KELAS V SD NEGERI 10 SANUR - Ni Luh Sukanadi; Ida Ayu Made Wedaswari (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2011)
The undertaking of this research was titled improving oh history comprehension achievement on the discussion method by the fifth grade students of SD Negeri 10 Sanur in academic year 2009/2010 that was background of the problems of the students low or poor on the history comprehension ability. Because, the research question of the present study was classificated of classroom action research (CAR) formulated as follow : what does the discussion method can be increase students ability by the fifth grade students SD Negeri 10 Sanur on academic year 2009/2010 on the history comprehension achievement?. The theoretical framework which is used in present study includes of a literature meaning, kind of prose, a history meaning, kind of history, the elements of history, feedback to students about history, and discussion method. This study was made using classroom action research with perfected or increased study practice so that be batter. The result of research showed that the discussion method can increased students ability on the history comprehension achievement. Because of, can showed from first test scores, final test cycle I, final test cycle II, and final test cycle III. Where, on precycle (first test) scores showed the subjects figure of 4,32 increased of 42,82%, on cycle I became 6,17, on cycle II of 19,12% became 7,35, and back up be 24,76% , on cycle III was 9,12.